The heritage of Taras Shevchenko: the image of the "artist-prophet" in Ukrainian culture - A. I. Kretov, (Ukrainian Cultural Studies, 2020)
The article is devoted to the problem of the image of the artist as a prophet in connection with the work of Taras Shevchenko, due to his extraordinary influence on Ukrainian culture. The formation of this image is the result of the interaction of a number of socio-cultural factors, which are the subject of analysis in this article. First of all, it is the dependence of the Great Kobzar's self-determination on those strategies that depend on poetry and painting, the place of these spheres in contemporary society, their task of integrating creative activity into the social structure and artistic environment, the importance of skill and order. Secondly, the echo in the Shevchenko era of the ideas of the Enlightenment with their universalist claims and the emergence of a phenomenon in the Russian Empire, which was called "intelligentsia", formed against the background of cultural "literary centrism". Third is the influence of romanticism on the artist's idea of leading the process of forming a certain community, which is not associated with social inequality and formal hierarchies in society. Fourth is the dependence of the artist image – the prophet with the intertwining of Christian and pagan roots of Ukrainian culture. It is shown that the archetype of the national artist-prophet created by T. Shevchenko's successors survived situations of imitation, affirmation, rethinking, even denial. Such a diverse dialogue testifies to the urgency of Taras Shevchenko's legacy. The article shows that there is an urgent need to study the figure of Shevchenko in the context of world culture, the functioning of the model "artist – prophet" in general and in their own country. It is also important to give this problem a philosophical depth. It is necessary to comprehend the models through which they tried to attract the figure of Shevchenko to various ideologies, that is, to give it a certain "plane" and "one-dimensionality." And "one-dimensional" Taras Shevchenko is a model that is too easy to manipulate.
Keywords: artist as a prophet, poet, painter, community, society, "intelligentsia", literary centrism